APPLICATION OF PICTURE & PICTURE MODEL IN INTRODUCING ENGLISH VOCABULARY (NUMBER) AT EARLY CHILDHOOD (Case Study in term of Motivation Aspect) - ratna purwanti purwanti (Universitas Lambung Mangkurat, 2021)
The golden age is a sensitive period that is very important for children to develop all aspects of development such as language, one of which is English so they can compete in the global world while growing up. Introducing activity must be carried out with a learning model that is and are concrete so that children can understand what is meant for example the picture and picture model learning. This study aims to describe how the contribution of the application of picture and picture model in introducing English vocabulary (number) at early childhood to increase children's motivation. The research approach used is qualitative with the type of case study (case study). Data collection using in-depth interview, observation and documentation. The result showed that the application of picture and picture model in introducing English vocabulary (number) contribute to the improvement of children's motivation such as children's attention during activity (attention), children's interest in English (interest), trust the child's self in knowing English vocabulary (confidence) and the satisfaction with fun learning (satisfaction). This research can be used as input for the teacher to create English learning that can increase children's motivation in class.